KEPERIBADIAN ISLAM DAN PROFESIONALISME DALAM PEKERJAAN: SATU ANALISIS TEORITIS: Islamic Personality and Professionalism at Work: A Theoretical Analysis - Ghozali, Mohammad; Kamri, Nor ‘Azzah (Jurnal Syariah, 2017)
Issues of inefficiency and integrity at work show the increasingly demand on quality and professionalism. However, professionalism itself does not enough to produce a quality output. It must be accompanied by an Islamic personality. The combination of Islamic personality and professionalism is believed to contribute a maximum impact on the work quality. This article attempts to examine the concept of personality from Islamic perspective, its relation with professionalism and their implications in the employment context. For that purpose, qualitative study was carried out on the relevant literatures. Based on literatures, the study found that there is a close relationship between Islamic personality and professionalism. Thus, both Islamic personality and professionalism should be given attention because it provides positive implications on work quality in the organization.